ANALISIS FAKTOR KEPAHAMAN PERAWATAN DAN SERVIS TEKANAN UDARA PADA BAN SEPEDA MOTOR YANG MEMPENGARUHI KONSUMSI BAHAN BAKAR - Permana, Muhammad Priya (Pendidikan Vokasional Teknologi Otomotif, Universitas PGRI Yogyakarta, 2024)
According to data from Statistics Indonesia 2023 in the upload of the Central Statistics Agency (BPS), in 2022 in Indonesia there were approximately 125.3 million motorcycle units. For several years from 2012 to 2022 it was noted that the number of motorcycles had increased by about 48.9 million units, this means that there has been an increase of about 64%. The main objective of this research is to analyze one of the factors of misunderstanding maintenance and servicing, namely the filling of air pressure in tires, which results in greater fuel consumption (cost). The abnormal state of tires affects the performance of the vehicle to be optimal and efficient. This research uses quantitative research methods. The data obtained was obtained from a survey conducted by the research to the existing sample. The survey was conducted based on several classifications regarding the understanding of motorcycle users' air pressure. The qualifications are (1) Gender; (2) Age; (3) Type of Work; and (4) Driver's License Ownership. The indicators that have been described are influenced by several dominant things. For the maintenance of filling the air pressure in the tire, the dominant qualifications are (1) Male (62.5%); (2) Age 16 - 35 years (38%); (3) Occupation type TNI / Polri (23.6%); and (4) Having a driver's license (67%). As for knowledge about the energy and cost effects of low air pressure are (1) Fuel costs per month 100,000 - 500,000 (82%); (2) Motorcycle mobility 10 - 50 KM (52.3%), (3) Frequency of filling air pressure > 1 month (45%); and (4) Many who answered yes to know the risks of low air pressure (69%). Keywords: Ignorance of Maintenance and Service, Tires.